DDRE-17. A PHASE I CLINICAL TRIAL OF DOSE-ESCALATED METABOLIC THERAPY COMBINED WITH CONCOMITANT RADIATION THERAPY IN HIGH-GRADE GLIOMA. (25th March 2021) - Porper, Keren; Shpatz, Yael; Plotkin, Luba; Pechthold, Ronit Goldman; Talianski, Alisa; Hemi, Rina; Mardor, Yael; Jan, Elisheva; Genssin, Hili; Symon, Zvi; Yair, Anikster; Zach, Leor; et al.
Abstract: BACKGROUND: Animal brain-tumor models have demonstrated a synergistic interaction between radiation therapy and a ketogenic diet (KD). Metformin has in-vitro anti-cancer activity, through AMPK activation and mTOR inhibition. We sought to assess the feasibility of combined radiation, KD and metformin in adults with high grade gliomas. METHODS: A prospective single-institution phase I clinical trial of combined metabolic therapy and radiotherapy. Radiotherapy was either 60Gy over six weeks or 35Gy over two weeks for newly diagnosed and recurrent gliomas, respectively. The dietary intervention consisted of a KD supplemented with medium chain triglycerides (MCT). There were three cohorts 1) dietary intervention alone, 2) low-dose metformin combined with dietary intervention and 3) high-dose metformin combined with dietary intervention. Clinicaltrials.gov NCT02149459. RESULTS: A total of 13 patients were accrued, median age 61 years, of whom 6 had newly diagnosed and 7 with recurrent disease. All completed radiation therapy; 5 patients stopped the metabolic intervention early. Metformin 850mg three-times daily was poorly tolerated. There were no grade 4 / 5 adverse events, and only one grade 3 event (nausea). The median level of ketones during the intervention was 0.5 mM. Ketone levels were associated with dietary factors (high fat, low carbohydrates, MCT intake), use of metformin and low insulin levels. Median progression free survival was 10 months for newly diagnosed disease and 4 months for recurrent disease. CONCLUSIONS: The intervention was fairly well tolerated, however only moderate ketones levels were obtained. Metformin use and dietary intake were associated with higher serum ketone levels. The recommended phase II dose is the 8 weeks of a low-carbohydrate diet combined with 850mg metformin twice daily.